1990
DOI: 10.1152/ajpgi.1990.259.1.g99
|View full text |Cite
|
Sign up to set email alerts
|

Development of L-glutamine-stimulated electroneutral sodium absorption in piglet jejunum

Abstract: Glutamine is the primary metabolic fuel of the small intestine. To determine the effects of glutamine on intestinal electrolyte transport, piglet (3 days to 3 wk old) jejunum was bathed in Ussing chambers in a buffer containing 10 mM serosal glucose, and the effects of different concentrations of mucosal L-glutamine and D-glucose on short-circuit current and transmucosal Na+ and Cl- transport were measured. Resting jejunum secreted Na+ and Cl- in an electrogenic manner. In contrast to mucosal D-glucose (30 mM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 0 publications
2
25
1
Order By: Relevance
“…The epithelial conductance (G) increased with addition of Val (5, 10 and 20 mmol Val/L), which is in accordance with the Isc response to Val addition. The increased G indicates that the Val increased the permeability of the epithelial tissue and confirms other Ussing chamber studies with pig epithelium after adding L‐glutamine (Rhoads, Keku, Bennett, Quinn, & Lecce, ) and L‐alanine (Rhoads, MacLeod, & Hamilton, ). The increased Isc in response to Val is in accordance with earlier observations on the effect of AA's in pig's small intestine (Grøndahl, Munck, & Skadhauge, ; Grøndahl & Skadhauge, ).…”
Section: Discussionsupporting
confidence: 86%
“…The epithelial conductance (G) increased with addition of Val (5, 10 and 20 mmol Val/L), which is in accordance with the Isc response to Val addition. The increased G indicates that the Val increased the permeability of the epithelial tissue and confirms other Ussing chamber studies with pig epithelium after adding L‐glutamine (Rhoads, Keku, Bennett, Quinn, & Lecce, ) and L‐alanine (Rhoads, MacLeod, & Hamilton, ). The increased Isc in response to Val is in accordance with earlier observations on the effect of AA's in pig's small intestine (Grøndahl, Munck, & Skadhauge, ; Grøndahl & Skadhauge, ).…”
Section: Discussionsupporting
confidence: 86%
“…Studies by Rhoads et al [51] and Argenzio et al [52] have consistently demonstrated that glutamine drives significant sodium absorption in piglet intestines infected with Cryptosporidium despite the two-thirds reduction of ileum surface area. Perhaps the most striking finding of these studies was the demonstration that glutamine was twice as effective as glucose in inducing NaCl absorption in infected pigs (2.8 ± 0.8 vs 1.4 ± 1.1 µEq/h/cm 2 , Na + net flux driven by glutamine and glucose, respectively) and restored Na + transport to uninfected control levels (2.1 ± 1.1 µEq/h/ cm 2 ) [52].…”
Section: Glutamine Effects On Cryptosporidiosismentioning
confidence: 97%
“…Infected piglets at 8, 12, and 16 d of age were compared with control animals aged 8-10, 10-13, and 14-19 d. We did not study uninfected and rotavirus-exposed piglets concurrently because rotavirus outbreaks occur despite assiduous disinfection of the facility. Some of the enzyme and morphologic data for uninfected animals were reported in previous studies (12,15).…”
Section: Animalsmentioning
confidence: 90%